THE CORRELATION OF KNOWLEDGE AND ATTITUDE WITH GIVING COLOSTRUM TO NEWBORN IN PUSKESMAS TAPING HILIR II RIAU INDONESIA - Enita Deriana Sagala; Eka Purnama Sari; Riska Susanti Pasaribu; Lasria Simamora; Ridesman Ridesman (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
A common problem is the bad habits of Indonesian mothers when it comes to breastfeeding, namely giving their babies breast milk with white color and thick yellow liquid or colostrum which is thrown away because it is considered a cause of pain. This study used a quantitative descriptive method. The design used in this study was